Еволюція корпоративної соціальної відповідальності в науковому дискурсі: бібліографічний аналіз - Oliinyk, Olena O. (Institute of Industrial Economics of NAS of Ukraine, 2025)
The purpose of the scientific article is to study the evolution of corporate social responsibility based on a bibliographic analysis of scientific research using the Scopus scientometric database. The bibliographic analysis was conducted using the VOSviewer 1.6.20 software product. The Scopus scientometric database was chosen as the information base for the study as one of the most authoritative multidisciplinary platforms for scientific research. Extrapolation and economic and mathematical modeling methods were used to predict the number of scientific research on CSR in the coming years. The study of the features of CSR implementation at each stage of its development was carried out using cluster analysis. The keyword “corporate social responsibility” was chosen to search for scientific publications in the Scopus scientometric database. The revealed evolution demonstrates the gradual development of CSR from local initiatives to global strategies for sustainable development. At the initial stage, the researchers focused on ethics, social behavior, human rights, and the interaction of business with society. Subsequently, research has become more global, with the integration of environmental and social aspects into business practice, with a focus on transparency, marketing, environmental sustainability and global reporting standards. The period 2020—2024 is marked by the adaptation of business to global crises: the COVID-19 pandemic, social inequality, environmental threats and gender diversity. The practical value of this research lies in the formation of a comprehensive understanding of the development of corporate social responsibility and sustainable development in different time contexts, which will allow business, governments and other stakeholders to respond more effectively to the challenges of modernity. Future research in this area will concern the study of socially responsible practices in different countries or regions, in particular in war conditions. This will allow identifying local barriers and successful cases for the further development of CSR. The language of the article is Ukrainian.